Identification The Content of Lead (Pb), Mercury (Hg), Chlorophyll-a, and Cell Morphology of Seaweed Kappaphycus alvarezii in Bluto and Saronggi Water, Sumenep, Madura, East Java - Aisyah Afrianti; Farah Nabilah; Reysa Sasmaya Wahyadyatmika; Moch. Amin Alamsjah; Agustono Agustono; Abdul Manan; Boedi Setya Rahardja (Universitas Airlangga, 2019)
Kappaphycus alvarezii is one of Indonesia's export commodities because it has high economic value as food and industry. One area in East Java which is the center of seaweed cultivation is Sumenep regency such as Saronggi and Bluto. Currently Sumenep Regency is an area for oil and gas exploration and exploitation. Types of pollutants resulting from these activities cause pollution in aquatic environments such as lead (Pb), mercury (Hg) and cadmium (Cd). The heavy metals found in the waters can be absorbed and accumulated in the seaweed thallus. The purpose of this research is to know the heavy metal content of Pb, Hg, Cd, chlorophyll-a, and cell morphology in E. cottonii in Bluto and Saronggi waters. This research is survey and descriptive research. The results showed that there are differences in heavy metal content of lead in E. cottonii, seawater, and sediments in Bluto waters and Saronggi waters. The waters of Bluto have a lower amount of chlorophyll-a than the Saronggi Waters. Cell wall thickness in E. cottonii in Saronggi Waters has thinner cell walls than Bluto waters. Measurement of water quality in Bluto and Saronggi waters through temperature, pH, salinity, brightness and DO parameters. The measurement results from both waters are not any striking difference and under optimal conditions.